Amyloid, prions, and other protein aggregates - Wetzel, Ronald (Methods in enzymology, 1999)
This volume includes a core of methodologies to attack the unique experimental problems presented by protein misassembly. Emphasis is on human biology applications, the area in which there is the most interest, in which most of the work has already been done, and in which there is the best evidence for the structural sophisitication of the protein aggregates. The critically acclaimed laboratory standard for more than forty years, Methods in Enzymology is one of the most highly respected publications in the field of biochemistry. Since 1955, each volume has been eagerly awaited, frequently consu.